Prediksi dan visualisasi penyakit COVID-19 menggunakan kombinasi Prophet dan GeoPandas - Ardito Laksono Suryoputro; Sri Yulianto Joko Prasetyo (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2023)
Covid-19 is spreading very rapidly. Indonesia is one of the countries with the highest cases in Southeast Asia. The purpose of this research is to use machine learning models with the help of tools such as Prophet to predict the trend of the Covid-19 outbreak in Indonesia. Obtained data will be visualized using a Geographic Information System (GIS) with Geopandas, which is used to visualize the spread of Covid-19 in Indonesia. Predictions with three tuning methods using Prophet with trend flexibility and holiday effects scored the best, with 0.68 for RMSLE and 1070 for MAE. Based on the use of Geopandas for Covid-19 cases in Indonesia, Geopandas can be used to visualize geospatial data effectively.